Penerapan bentuk arsitektur tradisional Bali pada teater kesenian di Kabupaten Badung - Alan Darma Saputra; Rahadhian Prajudi Herwindo; Yohanes Karyadi Kusliansjah (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Bali Island is a famous tourist destination in the world and this has made it a gathering hub and multicultural meeting center for tourists from several countries, thereby, raising concern on the possibility of the area losing its traditional Balinese architecture. It is necessary to make adjustments by adopting the shape of the old Balinese building. This means the emergence of new functions is not a taboo but a new design challenge, therefore, the traditional Balinese architecture and theater provisions were combined to produce a neo-vernacular architecture by using descriptive qualitative method. This led to the application of Asta Kosala-kosali in the theater space, modification on the roof, body and legs shape of the Balinese building, and the integration of the construction system and materials in the Balinese theater architecture. © 2020 Alan Darma Saputra, Rahadhian Prajudi Herwindo, Yohanes Karyadi Kusliansjah